Defining postverbal prepositional phrases in Chinese - Lister, Anthony C. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2008)
In this paper I examine the occurrence of prepositional phrases (PPs) in Chinese in postverbal position. The corpus was composed of 92 sentences taken from several Hong Kong newspapers that were published in 2004 and 2005, including Sing Tao Daily and Wen Wei Po.